The idea strategy in the theater (Al-Academy, 2018)
There is an association between the signifier and the signifier. This association shows the eyeball, which acquires a direct presence and whose presence influences the level of production of the hidden connotation. Because the theatrical presentation is a series of auditory-visual functions, these signs are looking for the exploration of their meanings and their evocation to form a complete loop to achieve the association of the above. This is what made the researcher to monitor the abundance of semantic shifts in theatrical presentation as long as the implications of the strategy continue in the game of semantic production with multiple horizons, and the idea in theatrical presentation tolerates multiple readings according to the references of the recipient and the relationship of the idea of ​​producing the meaning and relation of the idea with the remaining vocabulary of a plot, language, Or music is what will be given her presence or presence.The research included a systematic framework representing the problem of research and its importance, and defined the objective and limits of the research. In the theoretical framework, the researcher dealt with two topics: the first topic: the idea in the theatrical presentation, the second topic:In the course of the research, the researcher dealt with a descriptive sample that represented the play "Women of Lorca". He then reached a set of conclusions and conclusions. Then the summary of the research in English and the list of sources